Impelementasi problem based learning dalam mata pelajaran al-qur’an hadis pada peserta didik kelas viii-i mtsn 1 kediri - Jamil, Dina Rahmatun Najma (Maliki Interdisciplinary Journal, 2025)
This article discusses the implementation of the Problem Based Learning (PBL) model in the subject of Al-Qur’an Hadith at MTsN 1 Kediri. PBL is a learning method that emphasizes problem-solving and skill development for students. The PBL learning model is described as a stategy to enchance students understanding, critical thingking skills, and problem-solving abilities. Problem based learning presents real-life situations that require student investigation to find solutions. The article also outlines the steps of implementing PBL at MTsN 1 Kediri, starting from teacher preparation to final evaluation. The research findings indicate that PBL is effective in increasing student engagement in learning. By implementing PBL, MTsN 1 Kediri aims to improve the quality of education by utilizing relevant technology and curriculum. This article provides a deep understanding of the implementation of PBL in the context of Islamic education in madrasahs.